Changes in infection control practice for coronavirus disease 2019 (COVID-19) between 2020 and 2021: A nationwide questionnaire survey in Japan - Hitoshi Honda; Akane Takamatsu; Hiroki Saito; Koh Okamoto (Cambridge University Press, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has influenced current infection control practices in the healthcare setting. We surveyed 74 hospitals in Japan regarding changes in their infection control practices or policies between 2020 and the present. We found that the current hospital infection control practices for COVID-19 are adequate.